Team Resilience as a Second-Order Emergent State: A Theoretical Model and Research Directions - Bowers, Clint; Kreutzer, Christine; Cannon-Bowers, Janis; Lamb, Jerry (Frontiers in Psychology, 2017)
Resilience has been recognized as an important phenomenon for understanding how individuals overcome difficult situations. However, it is not only individuals who face difficulties; it is not uncommon for teams to experience adversity. When they do, they must be able to overcome these challenges without performance decrements. This manuscript represents a theoretical model that might be helpful in conceptualizing this important construct. Specifically, it describes team resilience as a second-order emergent state. We also include research propositions that follow from the model.